Patterns of Psychological Distress and Well-Being among Adults in Relation to Gender during COVID-19 Pandemic - Arora, Ameya; Sharma, Pankhuri; Verma, Nitin Kumar (Homœopathic Links, 2021)
Coronavirus disease-2019 (COVID-19) pandemic has led to the worsening of mental health of people in terms of increased psychological distress and decreased psychological well-being. The study was designed to understand the influence of COVID-19 pandemic on psychological distress and well-being. Present study also explored the variances in psychological distress and well-being in relation to development stages (young adulthood and adulthood), gender (males and females), people who had been infected by coronavirus and those not infected, and respondents whose immediate family members/relatives/friends/classmates had been infected by coronavirus and those not infected. An online survey was conducted in the midst of the pandemic. Responses of 250 respondents were gathered and analysed using the General Well-being Questionnaire developed by Veit and Ware in 1983. The results indicated that COVID-19 pandemic played a significant role in determining psychological distress and well-being. Gender differences in psychological distress and well-being are present with males being high on psychological distress and females being high on psychological well-being. Adults were found to be high on psychological distress than young adults. It was also revealed that as a person (respondent himself/immediate family/friends/relatives) becomes infected and recovers, their psychological distress declines, and well-being increases, probably because of reduced fear of being infected again. Along with other demographic variables, developmental stages and gender differences also played a crucial role in psychological distress and well-being of adults.
Keywords: adults; COVID-19; development stages; gender differences; psychological distress; psychological well-being; young adults